Was bringt eine geänderte Ertragskompetenz bei der Einkommensteuer? Eine Replik - Alfred Boss; Reinhold Weiß; Werner Münzenmaier; Christoph Weber (Wirtschaftsdienst, 2014)
In der Aprilausgabe 2014 veröffentlichte der Wirtschaftsdienst einen Aufsatz mit dem Titel Neuordnung der Besteuerungskompetenzen bei der Einkommensteuer. Die Autoren des vorliegenden Beitrags setzen sich kritisch damit auseinander, im Anschluss erläutern Gisela Färber, Carsten Kühl und Denis Alt ihren Standpunkt in einer Erwiderung. – – The Reply: The reform proposal would complicate the rules for sharing income tax revenues. The measures proposed are not compatible with the rules set out in the German Federal Constitution and the relevant decisions of the Constitutional Court. The states would lose tax revenues, whereas the federal government would gain them. As to individual states, the financially strong ones would be the losers, despite the fact that economic strength and fi nancial strength should be signifi cantly related. The Response: Future fi scal equalisation in Germany requires not only a new equalisation formula but also a fairer, more equal, broader and more transparent tax base for states and local governments. If necessary, changes to the Federal Constitution should be undertaken to achieve a more equal vertical assignment of tax powers. The actual reform discussion should not be a confrontation between rich and poor states but should lead to a fi nancial constitution by 2020 which can be unanimously approved by all of the German states.
Keywords: H11; H24; H7; 330; Einkommensteuer; Besteuerungsverfahren; Steuerreform; Deutschland